2018
DOI: 10.5004/dwt.2018.22336
|View full text |Cite
|
Sign up to set email alerts
|

MBD of grey prediction fuzzy-PID irrigation control technology

Abstract: a b s t r a c tFor the water and fertilizer ratio adjustment, irrigation control precision and problems and development cycle in the agricultural water-fertilizer irrigation, the control model of the combination of proportion-integral-derivative (PID) control, fuzzy control and grey prediction control were designed, and the controller design was carried out based on the model design method. It can achieve the engineering code to the embedded hardware requirements of the whole process of automation, efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Conventional PID control and fuzzy PID control can hardly avoid the overshoot and ensure the stability of the system. In our research a grey prediction model is adopted, which replaces the input of the PID method with the prediction value instead of the feedback value to reduce the overshoot and improve the stability of the system [31,32].…”
Section: Fuzzy Pid Temperature Control Based On Grey Prediction Modelmentioning
confidence: 99%
“…Conventional PID control and fuzzy PID control can hardly avoid the overshoot and ensure the stability of the system. In our research a grey prediction model is adopted, which replaces the input of the PID method with the prediction value instead of the feedback value to reduce the overshoot and improve the stability of the system [31,32].…”
Section: Fuzzy Pid Temperature Control Based On Grey Prediction Modelmentioning
confidence: 99%
“…For complex PID parameter tuning problems, many scholars use swarm intelligence algorithms to optimize PID controller parameters. Zhang et al 25 designed a control model combining PID control, fuzzy control, and gray predictive control for water-fertilizer ratio adjustment and irrigation control accuracy in agricultural water-fertilizer irrigation. Hekimoglu et al 26 proposed the atomic Search Optimization (ASO) algorithm and its modified version to determine the control parameters of the PID controller for motor speed.…”
Section: Related Workmentioning
confidence: 99%
“…China introduced water-saving irrigation technology from developed countries decades ago, yet the technology is used infrequently in the total irrigated area in China. The literature [18] proposed a water diffusion controller using fuzzy control logic, and the experimental results showed that the controller designed by it has a remarkable effect in this regard. This paper is divided into three parts to discuss the intelligent agricultural irrigation control platform based on PLC technology.…”
Section: Introductionmentioning
confidence: 99%